Biaxial failure response of composite laminates - Gan, Samuel Shi Guang (2017)
The increasing applications of composite materials in many complex structures from aircraft fuselage to high performance automobiles could result in multi-axial stresses on the equipment surface during the operating processes. Previous experiments performed from conventional uniaxial testing methods may limit the growing sophisticated use of this desired material. Long fibre reinforced composite materials are usually characterised based on single loading criterion, whereas in practice the loading during service is multi-axial. Recently, many biaxial tests were conducted with realistic loading conditions to further maximise composites’ applications. However, there were still insufficient reliable composite materials’ biaxial test data due to the material anisotropic properties and the high costs to conduct the tests. In this study the author fabricated Glass Fibre Reinforced Polymer (GFRP) cruciform specimens to perform the various biaxial loading configurations to investigate the failure behaviour of the specimens. The Instron® universal testing machine (UTM) carried out the biaxial loading on the mounted specimen with in crack opening mode and shearing mode to obtain the fracture toughness results. Besides that, three type of adhesive joints were also designed and fabricated to be clamped in between the modified Arcan test jig to test the fracture characteristics of quasi isotropic GFRP laminates. The ABAQUS® finite element analysis software simulates numerical finite element to derive the geometrical factors. The critical loads from the experiments along with the geometrical factors were used to compute the critical stress intensity.